Media Studies the basics - McDougall, Julian; Pollard, Claire (Routledge, an imprint of the Taylor & Francis Group, 2020)
"Fully updated and revised, the second edition of Media Studies: The Basics is the ideal guide to the changing landscape of media and media studies. There have been seismic shifts in what constitutes (the) media in recent years with technological advances ushering in whole new categories of producers, consumers and modes of delivery. This has been reflected in the way media is studied with new theories, concepts and practices coming to the fore. This new edition addresses core questions including: Who, or what, are the media? What are the key terms and concepts used in analysing media? Where have new media technologies had the biggest impact? How, and by whom, is media made in the 21st century? Featuring new case studies, an updated glossary and suggestions for further reading, this is the ideal introduction to media studies today for both A Level and Undergraduate students."--Provided by publisher.